RESEARCH OF LANE CHANGE PATTERNS TAKING INTO ACCOUNT OF THE DRIVER’S FUNCTIONAL STATE - Prasolenko, O.; Chumachenko, V. (Municipal economy of cities. Series: «Economy science», 2025)
The article considers the issue of assessing traffic safety in places of conflict situations of transport infrastructure. Conflict zones of transport infrastructure are considered to be places where drivers have no opportunity to avoid a traffic accident (traffic accident) unless a braking or acceleration maneuver is performed. As a result of the driver’s actions during maneuver or braking, critical longitudinal and transverse accelerations occur, and a conflict situation arises. Each conflict situation has its characteristics. It is proposed to use the mutual influence of longitudinal and transverse acceleration to determine the strength of the conflict situation. Experimental studies of the influence of road conflicts on the functional state of the driver (change in respiratory rate, skin conductivity) showed the relationship between the strength of the conflict situation and the driver’s energy expenditure after getting into danger and performing actions. The influence of mild, moderate and critical conflicts was considered, with a distinction based on deceleration parameters. It is proposed to use the “combined acceleration” as the force of the conflict, determined by the mutual influence of longitudinal and transverse acceleration during the conflict. The influence of the force of the conflict situation on the driver’s energy expenditure and the shift of the skin-galvanic reaction, which characterizes the driver’s emotional stress, is quantitatively substantiated. In critical road conflicts, the driver’s energy expenditure increased to 4.7 Kcal/min and the shift of emotional stress to 3.2 units. The paper presents an approach to determining the driver’s emotional stress based on energy expenditure, heart rate shift, and skin-galvanic reaction shift when getting into road conflicts. To determine road conflicts, a GPS-based vehicle motion parameters registration system was used, which allows recording speed, longitudinal and transverse acceleration with a frequency of 10 units per second. As a rule, lane changes were performed under the condition of a safety gap (the time interval when there was a gap between vehicles in the adjacent lane), then the driver performed the lane change within a certain period. The driver performed the lane change strictly under the condition of safe execution. If the conditions were characterized as dangerous, the driver did not perform the lane change maneuver. Using the recording equipment, it was determined how much time the driver spent on changing lanes. The speed of movement was from 40 to 50 km/h. In other cases, when the time was greater or less, this was due to the conditions for performing the lane change, as well as traffic safety. What is characteristic is that when the driver needed to change the lane, the response was always a change in GSR, that is, the driver performed a conscious action to change the lane. Thus, the driver formed a motive for how to quickly change the lane. This depended on the speed of the traffic flow, and the emotional stress of the driver. In addition, the faster and sharper the lane change maneuver, the greater the shift in heart and respiratory rates. Thus, the driver, performing the lane change maneuver, guided by his goals (choosing the direction of movement at the intersection, choosing a free lane, overtaking a vehicle with a slower speed in front), carried out purposeful activity to realize his need. Shifts in galvanic skin response, heart rate, energy expenditure indicate that the less time drivers spend on changing lanes, and the situation that prompted them to the maneuver, the greater the emotional stress.